Gratitude in Organizations: A Contribution for Healthy Organizational Contexts - Di Fabio, Annamaria; Palazzeschi, Letizia; Bucci, Ornella (Frontiers in Psychology, 2017)
This article reviews the construct of gratitude. Gratitude has been shown to be a fundamental resource for strengthening individual wellbeing. From a positive psychology perspective, gratitude is recognized as a promising opportunity for individuals because it can be enhanced through specific training according to a primary prevention framework. In organizations, gratitude is now thought to be crucial to employees’ efficiency, success, and productivity while also improving organizational citizenship behaviors, prosocial organizational behavior, and the organizational climate. Thus, gratitude is noteworthy because it increases positive relationships, social support, and workers’ well-being, reduces negative emotions at the workplace, and enhances organizational health and success. This perspective article concludes by suggesting new directions for gratitude research and intervention in the organizational context.